2018
DOI: 10.1002/aelm.201800683
|View full text |Cite
|
Sign up to set email alerts
|

Over 6% Certified Sb2(S,Se)3 Solar Cells Fabricated via In Situ Hydrothermal Growth and Postselenization

Abstract: eV), [1][2][3] remarkable absorption coefficient (≈10 5 cm −1 ), [4,5] excellent stability, and low-toxicity component. To promote the power conversion efficiency, many methods have been successfully applied to fabricate Sb 2 (S x ,Se 1-x ) 3 solar cells. For example, the rapid thermal evaporation (RTE) method [6] have been gathered many attentions for the fabrication of Sb 2 Se 3 solar cells. Recently, Tang and co-workers used a novel vapor transport deposition (VTD) way to refresh the recorded efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 57 publications
3
66
0
Order By: Relevance
“…Studies revealed that Sb 1.9 S 2.2 Se 0.9 has a bandgap of 1.52 eV, falling into the ideal bandgap in the Shockley–Queisser limit. During the publication of the review, a certified PCE of 6.14% and a record efficiency of 6.3% for Sb 2 (S x Se 1−x ) 3 solar cells were realized by using hydrothermal method and VTD method to fabricate Sb 2 (S x Se 1−x ) 3 films, respectively …”
Section: Antimony Chalcogenide Solar Cellsmentioning
confidence: 99%
“…Studies revealed that Sb 1.9 S 2.2 Se 0.9 has a bandgap of 1.52 eV, falling into the ideal bandgap in the Shockley–Queisser limit. During the publication of the review, a certified PCE of 6.14% and a record efficiency of 6.3% for Sb 2 (S x Se 1−x ) 3 solar cells were realized by using hydrothermal method and VTD method to fabricate Sb 2 (S x Se 1−x ) 3 films, respectively …”
Section: Antimony Chalcogenide Solar Cellsmentioning
confidence: 99%
“…[1] However, due to limited abundance of some of its constituent elements, it is essential to seek earth-abun-In comparison, the best efficiencies in Sb 2 S 3 solar cells were commonly realized by means of solution-based methods, such as chemical bath deposition (CBD), spin coating and hydrothermal synthesis. [2,[10][11][12][13] The record efficiency of 7.5% for Sb 2 S 3 solar cells, achieved in sensitized Sb 2 S 3 on mesoporous TiO 2 , has remained stagnant since 2014. [2] Despite extensive studies on new hole transport materials (HTMs), absorber doping, interface engineering and anion substitution devoted to enhance the Sb 2 S 3 device performance, [2,10,[14][15][16][17][18] the fundamental question associated with optimal crystal orientation, which is crucial for Sb 2 S 3 solar cell performance, still remains unresolved in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The opaque device with Au electrode was first applied to make optimization. Sb 2 S 3 thin films were synthesized by hydrothermal deposition method at 135 °C according to the reported method with modifications (see Experimental Section for details) . Typically, the as‐synthesized Sb 2 S 3 films show flat surface morphology (Figure a and Figure S1, Supporting Information).…”
Section: Photovoltaic Parameters Of Semitransparent Sb2s3 Cells With mentioning
confidence: 99%